Effect of phase in fast frequency measurements for sensors embedded in robotic systems. (16th August 2019) - Sanchez-Lopez, Juan de Dios; Murrieta-Rico, Fabian N; Petranovskii, Vitalii; Antúnez-García, Joel; Yocupicio-Gaxiola, Rosario I; Sergiyenko, Oleg; Tyrsa, Vera; Nieto-Hipolito, Juan I; Vazquez-Briseño, Mabel
The use of sensors is a primary need in robotic systems. There are sensors that generate a signal whose frequency depends on input stimulus. The application of such sensors is desirable due to their short response time, accuracy, and resolution. For proper use of these sensors, adequate frequency measurement is required. The principle of rational approximations is a method for frequency estimation that has advantages over other measurement methods. Some of them include not a fixed sampling time, insensitivity to jitter, and accuracy limited by the reference stability. Nevertheless, there are some measurement parameters with a not well-researched effect in measurement process. The objective of this work is to elucidate how the phase of input signals (measurand and reference) affects the frequency measurement process.